2018
DOI: 10.22616/erdev2018.17.n045
|View full text |Cite
|
Sign up to set email alerts
|

Indicator-based analysis of socially sensitive and territorially sustainable development in relation to household energy consumption

Abstract: One of the major fields of actions in sustainable development is energy. The correlation between the number of renewable energy sources and selected socioeconomic variables was already analysed, however, other energy indicators used for sustainable development assessment should be also checked. This issue is especially important outside the biggest cities in Poland due to the different energy use in relation to the density of urban development. The aim of the study is to identify the correlation between the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The research findings on airport externalities have several practical implications, as demonstrated in many recent papers [25]. Like many other papers on the nexus between environmental sustainability and economic development [61], our research related to the restrictions resulting from the introduction of limited use areas (LUAs) around two large Polish airports is a pioneering one, as it does not concern only acoustic damage. They are part of a wider problem related to the risk of airport management.…”
Section: Discussionmentioning
confidence: 56%
“…The research findings on airport externalities have several practical implications, as demonstrated in many recent papers [25]. Like many other papers on the nexus between environmental sustainability and economic development [61], our research related to the restrictions resulting from the introduction of limited use areas (LUAs) around two large Polish airports is a pioneering one, as it does not concern only acoustic damage. They are part of a wider problem related to the risk of airport management.…”
Section: Discussionmentioning
confidence: 56%
“…It was assumed that wood waste (edgings, sawdust, chips, shavings, etc.) account for approximately 20% of the initial total intended for processing [27]: (2) …where: Z DT -wood resources from the processing of wood for energy purposes [tonnes ⋅ year -1 ] P -timber for industrial purposes [tonnes] Estimated in this way, resources are converted into units of energy, taking the energy value of dry wood at 18.72 GJ • t -1 [27]. A limitation in using these resources for marketing is that a significant amount of waste generated during the processing of wood by processing industries is consumed for their own use by these plants.…”
Section: Methodsmentioning
confidence: 99%
“…There is a need to support the production of renewable energy. Development of and use of renewable energy resources has a positive impact on the environment [1,2], and it may also create local employment growth [3]. However, efficient energy management should provide energy not only for current generations but also for the future [4], and such management should minimize negative impact on the environment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The agriculture sector is considered part of a strategy for the mitigation and recovery of CO 2 , as codified in the acronym AFOLU (Agriculture, Forestry and Other Land Use) of the WGIII [1,4]. Other studies have deepened the topic of renewable energy sources, distinguishing phenomena Sustainability 2020, 12 and analyzing rural and urban areas (districts) [5] or for different urban density conditions [6]. In general, the scientific research is currently divided into two principal topics: the first focused on city environmental problems [7][8][9] and the second focused on GHG emissions in relation to rural development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%